Reducing Wait Times and Enhancing Communication Boost Patient Satisfaction in Healthcare: Mengurangi Waktu Tunggu dan Meningkatkan Komunikasi Meningkatkan Kepuasan Pasien dalam Layanan Kesehatan - Herdiati, Meilisa Fani; Fitriyah, Hadiah (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines how waiting time and health literacy-sensitive communication (HL-COM) affect patient satisfaction in the executive outpatient unit of Hospital Z. Using a sample of 120 respondents and analyzing data with Partial Least Square (PLS) structural equation modeling, we found that waiting time negatively impacts patient satisfaction. However, HL-COM significantly moderates this effect, mitigating the negative impact of waiting time. These findings suggest that hospital management should focus on both reducing waiting time and improving doctor-patient communication to enhance patient satisfaction. Highlights: Negative Impact: Waiting time significantly reduces patient satisfaction. Moderating Role: HL-COM moderates the effect of waiting time on satisfaction. Management Focus: Reduce waiting time and enhance doctor-patient communication. Keywords: Patient satisfaction, waiting time, health literacy-sensitive communication, hospital management, Partial Least Square (PLS)